Analisis Profil Protein Darah Anak Kambing Peranakan Etawah Dengan Pemberian Pakan Substitusi Susu Sapi - Teguh Wicaksono; Gatot Ciptadi; Tri Eko Susilorini (Jurusan Produksi Ternak, Fakultas Peternakan, Universitas Brawijaya, 2017)
The objective of this study is to determine the protein profile of pre-weaning kids fed with cow's milk as a substitute for dam’s milk. The materials used were 18 Etawah Descendant (PE) kids born the twin at the age of 5-13 days from 3-4-year-old dams. This experimental design was a completely randomized design with three treatments with six replications per treatment, namely the control (T0) fed 100% goat’s milk, treatment 1 (T1) fed 50% goat’s milk and 50% cow’s milk, treatment 2 (T2) fed 100% cow’s milk. The protein profile serum was analyzed by sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) method, 12,5% of the resolving gel and 3% of the stacking gel were used. The protein profile of the 5-14 days old PE kids were 19 protein bands with the molecular weight ranging from 15-160 kDa. The kids fed with 100% goat milk (T0) and those substituted by 50% cow's milk (T1), it was produced 19 protein bands with molecular weights ranging from 15 kDa to 155 kDa, while those fed with 100 % cow's milk (T2), it was produced 17 protein bands with molecular weights ranging from 13 kDa to 160 kDa. It can be concluded that the dam's milk substitute using cow's milk at the 50% level does not affect the blood protein profile of goat kids, while the 100% substitute produces the different number and types of protein